Simulations of ultrasensitive whispering gallery mode optical microdisk resonators - Feng, Wanqi (Nanyang Technological University, 2022)
Healthcare is one of the most worried concerns in the 21st century, infectious illnesses, cancer and pathogen threaten lives incessantly. Especially the various kind of cancers, this second leading cause of death worldwide has taken 10 million lives away from the society every year. Thus, a rapid, accurate, economic label-free detection of the extremely small concentration of cancer biomarkers is essential. Whispering gallery mode (WGM) microcavity sensing is one of the most used technology in optical and acoustic applications. With proper tuning, a special property of WGM has found the coalesce of the eigenstates and eigenvalues at the point called exceptional point. Exceptional point sensor shows attractive characteristics in enhancing the sensitivity of the microcavity sensor. In this dissertation, we focused on the sensor operate at exceptional point, which is the special property of non-Hermitian complex matrix, it degenerates in quantum system and is coalesced by at least two eigenstates, resonant frequencies or energy levels. We also discussed the conventional optical microcavity sensor work at so-called diabolic point and compare exceptional point to diabolic point in order to obtain an enhanced sensitivity to the perturbation. The enhancement in sensitivity was observed at least 3.0011 times higher than the traditional diabolic point microcavity sensor.